A Phase I Trial of Dasatinib and Osimertinib in TKI Naïve Patients With Advanced EGFR-Mutant Non-Small-Cell Lung Cancer - Kim, Chul; Liu, Stephen V.; Crawford, Jennifer; Torres, Tisdrey; Chen, Vincent; Thompson, Jillian; Tan, Ming; Esposito, Giuseppe; Subramaniam, Deepa S.; Giaccone, Giuseppe (Frontiers in Oncology, 2021)
Background: Osimertinib is an effective first-line therapy option for EGFR-mutant NSCLC, but virtually all patients develop resistance. CRIPTO, through Src activation, has been implicated in resistance to EGFR tyrosine kinase inhibitor (EGFR-TKI) therapy. Dasatinib, a Src inhibitor, has shown preclinical synergy with EGFR-TKI therapy. Method: This is a single-arm phase I/II trial of osimertinib and dasatinib in treatment-naïve advanced EGFR-mutant NSCLC. A 3+3 design was used in the phase I to establish the recommended phase II dose (RP2D). Osimertinib 80 mg QD was combined with dasatinib 70 mg BID (DL2), 50 mg BID (DL1), 70 mg QD (DL-1), and 50 mg QD (DL-2). Results: Ten patients (DL2: 3, DL1: 6, DL -1: 1) were enrolled. 3 (50%) of 6 patients at DL1 experienced a DLT (grade 3 headaches/body pain, neutropenia, rash, one each). Common treatment-related adverse events included pleural effusion (n=10), diarrhea (n=8), rash (n=7), transaminitis (n=7), thrombocytopenia (n=7), and neutropenia (n=7). While the MTD was not determined by protocol-defined DLT criteria, DL-2 was chosen as the RP2D, considering overall tolerability. Nine (90%) patients had a PR, including 1 unconfirmed PR. Median PFS was 19.4 months and median OS 36.1 months. The trial was closed to accrual prematurely due to slow accrual after the approval of osimertinib as first-line therapy. Conclusions: The combination of dasatinib and osimertinib demonstrated anticancer activity. The treatment was limited by chronic toxicities mainly attributed to dasatinib. To improve the safety and tolerability of Src and EGFR co-inhibition, Src inhibitors with a more favorable safety profile should be utilized in future studies.